Clinical characteristics and predisposing factors of lung metastasis in sacral chordoma: a cross-sectional cohort study of 221 cases - Shi, Qianyu; Guo, Wei; Yu, Siyue; Xu, Jiuhui; Ji, Tao; Tang, Xiaodong (Frontiers in Oncology, 2024)
Limited studies are available on the topic of lung metastasis in sacral chordoma. The primary objective of this study was to investigate the prevalence, characteristics, associated factors, and prognosis of lung metastasis in sacral chordoma. In this study, a total of 221 cases with primary sacral chordoma that underwent surgical resection at our center were included. Comprehensive demographic information, imaging findings, and oncological evaluations were collected and analyzed. The prevalence of lung metastasis in the cohort was 19.5%, with the lung emerging as the predominant site of distant metastasis. Recurrent chordoma cases exhibited a significantly higher lung metastasis rate in comparison to newly diagnosed chordoma cases (33.33% and 12.76%, p=0.0005). Patients with lung metastasis had a larger tumor size, a higher proportion of previous sacral chordoma surgeries and a greater likelihood of postoperative recurrence.Risk factors of lung metastasis were tumor size and postoperative recurrence.Radiotherapy was a protective factor of lung metastasis in the cohort. Patients with lung metastasis exhibited decreased median overall survival (91 vs. 144 months for those without lung metastasis, p<0.05) and recurrence-free survival (27 vs. 68 months, p<0.001) times. In summary, the current study elucidated the prevalence of lung metastasis in sacral chordoma in a large cohort, and our results underscore the importance of regular and long-term postoperative follow-ups of sacral chordoma patients.